The history of an inferior good: Beer consumption in Germany - Benjamin Volland (Max Planck Institute of Economics, 2012)
The question whether alcohol in general, and different types of alcoholic beverages in particular (e.g., beer) are normal or inferior goods is a heavily disputed issue within economics and health research. Based on recently developed theories of preference adjustment this paper argues that the answer to this question may not be independent of the level of income itself. It therefore applies a gradual switching regression approach to aggregate beer consumption data in Germany from 1957 to 2007. This method allows elasticities to change over time, without prior specifications of the time and speed of adjustments. Results suggest that an important behavioral change is present in the data, as elasticities of beer demand shifted considerably between 1965 and 2004. In particular, they demonstrate that over this period beer shifted from being a normal to being an inferior good.
Keywords: D10; C22; 330; Beer demand; Inferior goods; Gradual switching regression